On the issue of developing and applying the model of the participant of Internet training - M. M. Nazar; D. S. Meshcheriakov (Academy of Cognitive and Natural Sciences, 2017)
The research focus is effective application of the online trainings participants' model. The goals of the research are to describe, analyze and develop the online trainings participants' model, the allocation system basic components of developed appropriate model. The object of research is educational system. Subject of research: basic principles of identification, development and practical use of the online trainings participants' model. Methods: theoretical analysis of contemporary sources of the topic of research, synthesis, comparison and synthesis of scientific data sources. As a result of research are drawn conclusions that the participant's model of internet-based trainings exists for description, explanation and increase of studies' process' efficiency, its individualization and flexibility. It makes the catalogue of basic development's possibilities of corresponding model. Spectrum of meaningful possible variants of participant's choice of distant group psychological work or learning comes forward the foundation for development and practical realization of educational influence.